Dystrophin R16/17 protein therapy restores sarcolemmal nNOS in trans and improves muscle perfusion and function - Junling Zhao; Hsiao Tung Yang; Lakmini Wasala; Keqing Zhang; Yongping Yue; Dongsheng Duan; Yi Lai (BMC, 2019)
Abstract Background Delocalization of neuronal nitric oxide synthase (nNOS) from the sarcolemma leads to functional muscle ischemia. This contributes to the pathogenesis in cachexia, aging and muscular dystrophy. Mutations in the gene encoding dystrophin result in Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD). In many BMD patients and DMD patients that have been converted to BMD by gene therapy, sarcolemmal nNOS is missing due to the lack of dystrophin nNOS-binding domain. Methods Dystrophin spectrin-like repeats 16 and 17 (R16/17) is the sarcolemmal nNOS localization domain. Here we explored whether R16/17 protein therapy can restore nNOS to the sarcolemma and prevent functional ischemia in transgenic mice which expressed an R16/17-deleted human micro-dystrophin gene in the dystrophic muscle. The palmitoylated R16/17.GFP fusion protein was conjugated to various cell-penetrating peptides and produced in the baculovirus-insect cell system. The best fusion protein was delivered to the transgenic mice and functional muscle ischemia was quantified. Results Among five candidate cell-penetrating peptides, the mutant HIV trans-acting activator of transcription (TAT) protein transduction domain (mTAT) was the best in transferring the R16/17.GFP protein to the muscle. Systemic delivery of the mTAT.R16/17.GFP protein to micro-dystrophin transgenic mice successfully restored sarcolemmal nNOS without inducing T cell infiltration. More importantly, R16/17 protein therapy effectively prevented treadmill challenge-induced force loss and improved muscle perfusion during contraction. Conclusions Our results suggest that R16/17 protein delivery is a highly promising therapy for muscle diseases involving sarcolemmal nNOS delocalizaton.